Fermented Kangkong (Ipomoea aquatica Forssk) Juice: It’s Potential as Water Supplement on the Production Performance of Growing Japanese Quails - Ampode , Keiven Mark B. (Current Topics in Agricultural Sciences Vol. 4, 2021)
Quail raising is said to be the business venture of those with limited capital but who look for high returns in a short period of time. The meat and eggs of these birds are readily available for human consumption due to their high reproduction capability. A feeding trial to assess the growth performance and economic benefits of Japanese quails supplemented with varying levels of fermented kangkong juice through the drinking water was conducted using 120 female Japanese quails at the Department of Animal Science-College of Agriculture and Food Science, Visayas State University, Visca, Baybay City, Leyte, Philippines from January to February 2016. The Japanese quails were randomly assigned to four treatments and replicated three times with ten birds per replication laid out in a Completely Randomized Design set-up. Data gathered were subjected to a one-way analysis of variance (ANOVA) using Statistical Package for Social Science (SPSS) version 17.0 software. Supplementation of fermented kangkong juice (FKJ) into the drinking water of Japanese quails did not significantly affect the growth performance in terms of the results on bi-weekly weight gain, average daily gain, bi-weekly voluntary feed intake, and cumulative feed conversion ratio. However, the overall result on return above feed and chick cost (RAFCC) disclosed a bright prospect of FKJ supplementation for raising Japanese quails.